0115 Is gender adequately studied in agricultural workers' health research?. (23rd June 2014) - Habib, Rima R; Elzein, Kareem; Hojeij, Safa
Abstract : Objectives: Gender-sensitive research strategies address men's and women's health problems by identifying physiological, ergonomic and socio-cultural gender characteristics that shape study outcomes. These strategies have been inadequately accounted for in many occupational health researches on agriculture workers. In reviewing the occupational health literature on agriculture workers, this paper assesses the processes employed to analyse how gender affects work-related health outcomes. Method: Peer-reviewed articles concerned with male and female agricultural workers' health and published between 2000 and 2011 in PubMed were evaluated. Articles that use gender stratification were identified and analysed for their approaches toward sampling, data analysis, task differentiation and use of other exposure indicators. Results: Out of 176 articles, only 26 (15%) analysed the associations between occupational health exposures and health outcomes using gender stratification. Many studies failed to recruit adequate female participants or have marginalised gender at an early stage of the research. The role of females as homemakers was also inadequately conceptualised. Several others did not collect adequate task or exposure information to identify established risk factors relating to study outcomes. Conclusions: Occupational health research on farm workers struggle to incorporate gender analysis into research design and analytical approaches. The role of gender in shaping health outcomes is evident in occupational health research. Developing methodologies, study designs, and analysis that are gender-sensitive will improve the quality of research and help tailor sound interventions and policies. This could be through incentives and support from research funding agencies and through incorporating gender perspectives into academic journal editorial policies.